Tfcp2l1 safeguards the maintenance of human embryonic stem cell self‐renewal. Issue 9 (11th April 2018) - Sun, Hongwei; You, Yu; Guo, Mengmeng; Wang, Xiaohu; Zhang, Yan; Ye, Shoudong
Abstract : Tfcp2l1 is a transcription factor critical for mouse embryonic stem cell (mESC) maintenance. However, its role in human ESCs (hESCs) remains unclear. Here, we investigated the role of Tfcp2l1 in controlling hESC activity and showed that Tfcp2l1 is functionally important in the maintenance of hESC identity. Tfcp2l1 expression is highly enriched in hESCs and dramatically decreases upon differentiation. Forced expression of Tfcp2l1 promoted hESC self‐renewal. Functional analysis of the mutant forms of Tfcp2l1 revealed that both the CP2‐ and SAM‐like domains are indispensable for Tfcp2l1 to maintain the undifferentiated state of hESCs. Notably, the CP2‐like domain is closely related to the suppression of definitive endoderm and mesoderm commitment. Accordingly, knockdown of Tfcp2l1 significantly induced differentiation preferentially into definitive endoderm and mesoderm. Further studies found that inhibition of Wnt/β‐catenin signaling pathway by IWR1 is able to eliminate the differentiation caused by Tfcp2l1 downregulation. Taken together, these findings reveal the unique and crucial role of Tfcp2l1 in the determination of hESC fate and will expand our understanding of the self‐renewal and differentiation circuitry in hESCs. Abstract : Tfcp2l1 expression is highly enriched in hESCs and dramatically decreases upon differentiation. Forced expression of Tfcp2l1 promoted hESC self‐renewal, while knockdown of Tfcp2l1 induced differentiation.Our data reveal the unique and crucial role of Tfcp2l1 in hESC maintenance.